2015
DOI: 10.3109/21691401.2014.982800
|View full text |Cite
|
Sign up to set email alerts
|

The potential of archaeosomes as carriers of pDNA into mammalian cells

Abstract: This paper describes the formulation of archaeosomes and the evaluation of their abilities to facilitate in vitro DNA delivery. Lipids of the H.hispanica 2TK2 strain were used in archaeosome formation, which is formulated by mixing H.hispanica 2TK2 lipids with plasmid DNA encoding green fluorescent protein (GFP) or β-galactosidase (β-gal). Archaeosome/pDNA formation and unbound DNA were monitored by agarose gel electrophoresis. The archaeosome formulations were visualized by AFM and TEM. The zeta potential ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…For the latter, manufacturing of the surface localization of plasmid on lipid vesicles, plasmid DNA was surface-bound by incubating empty archaeosomes at 37 °C with shaking overnight. To improve complex formation between pDNA and archaeosomes, CaCl 2 as a helper molecule was also added into the medium 20 . In the end, the suspensions were sonicated…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the latter, manufacturing of the surface localization of plasmid on lipid vesicles, plasmid DNA was surface-bound by incubating empty archaeosomes at 37 °C with shaking overnight. To improve complex formation between pDNA and archaeosomes, CaCl 2 as a helper molecule was also added into the medium 20 . In the end, the suspensions were sonicated…”
Section: Methodsmentioning
confidence: 99%
“…They are more resistant to chemical hydrolysis, oxidation, bile salts, acidic or alkaline pH, and high temperatures with various vaccine and drug delivery applications 17 . Therefore, liposomes formed by archaebacterial membranes lipids represent a promising alternative to the classical liposomes and virosoms, consequently found extensive applications in vaccine and drug delivery [18][19][20] .…”
mentioning
confidence: 99%
“…Previous studies showed that the particles with zeta potentials <−30 mV are normally considered stable, and relatively high percentage of drug entrapment was recorded when compared to positively charged liposomes . In addition to this, if all the particles in a suspension have a large negative potential then they will tend to repel each other and have tendency to aggregate …”
Section: Resultsmentioning
confidence: 99%
“…In order to prepare archaeosome containing triptorelin acetate, we added hydrated medium containing mg of triptorelin acetate into the thin layer of lipid film, which was a homogeneous mixture of 5.42 mg cholesterol and 12.6 polar lipids of archaebacterial. Following that, sonication was performed for 10 minutes with a frequency of 60 Hz (Bandelin Sonorex Digitec) in order to harmonize the archaeosomes and preparation of a formulation with a better quality (17).…”
Section: Nanoarchaeosome Preparationmentioning
confidence: 99%